THE RELATIONSHIP BETWEEN UNEMPLOYMENT ANXIETY, DEPRESSION LEVELS AND ATTITUDES TOWARD FUTURE OF PROSPECTIVE PHYSICAL EDUCATION AND SPORTS TEACHERS - ABDULLA, DILSHAD HAVAL ABDULLAH (Fırat Üniveristesi, 2022)
Bu tez araştırması, örneklem grup çerçevesinde yükseköğretim düzeyinde spor eğitimi alan beden eğitimi ve spor öğretmeni adaylarının işsizlik kaygıları, depresyon düzeyleri ve geleceğe yönelik tutumları arasındaki ilişkileri ortaya koymak amacıyla In this study, the relationship between unemployment anxiety, depression level and attitude toward the future of prospective physical education and sports teachers were investigated. The study was conducted with 610 prospective physical education and sports teachers, who studied at Fırat University, Harran University, Adiyaman University, Agri Ibrahim Cecen University and Bayburt University. To determine the perspective of the study group, the "Unemployment Anxiety Scale", "Depression Scale" and the "Attitude Toward Future Scale" were used. The analyses of the data collected from the scale forms were conducted by using SPSS 24.0 package software. To reveal the distribution of the study group in terms of the demographical variables, frequency, and percentage calculations were conducted. To determine whether the data obtained from the scale and its subscales provided a normality distribution, a normality test was conducted. As a result of the normality test, it was decided to conduct parametric tests. To evaluate the level of differentiation in terms of the independent variables, parametric tests, which included "Independent samples t-test" and "One-way Variance Analysis (ANOVA)", were conducted. Additionally, "Correlation Analysis" was conducted to reveal the level and significance of the relationship between dependent variables. According to the results of the research, it was seen that there were statistically significant differences according to the variables of gender, school type, age, class, income status, father and mother education status, attitude towards the teaching profession, and the university where they received sports education. A positive and significant relationship was observed between the "Unemployment Anxiety Scale" and the "Depression Scale". Negative and significant relationships were determined between each of the "Attitudes towards the Future Scale" and the "Unemployment Anxiety Scale" and "Depression Scale". As a result, it is a worrying situation for the future of physical education and sports teaching that students studying at universities do not have a positive attitude towards their profession. It would be beneficial for university institutions to work together and prepare an action plan for the future to reduce employment.yapılmıştır. Araştırma, Fırat Üniversitesi, Bayburt Üniversitesi, Harran Üniversitesi, Ağrı İbrahim Çeçen Üniversitesi ve Adıyaman Üniversitesi'nde öğrenim gören 610 beden eğitimi ve spor öğretmeni adayı üzerinde yapılmıştır. Araştırma grubunun görüşlerini belirlemek amacıyla, ulusal/uluslararası düzeyde araştırmacılar tarafından geliştirilmiş üç adet ölçek formu kullanılmıştır. Ölçek formlarından elde edilecek verilerin analizleri, lisanslı SPSS 24.0 paket programı kullanılarak yapılmıştır. Araştırma grubunun, demografik değişkenlerine göre dağılımını ortaya koymak amacıyla frekans ve yüzdelik hesaplamalar yapılmıştır. Ölçekler ve alt boyutlardan elde edilen verilerin normallik varsayımını gerçekleştirip gerçekleştirmediğini görmek için normallik testi yapılmıştır. Bağımsız değişkenlere bağlı farklılaşma düzeyini değerlendirmek için parametrik verilerde "independent sample t-testi" ve "tek yönlü varyans analizi (ANOVA)" kullanılmıştır. Non-parametrik verilerde ise "Kruscal Wallis Testi" kullanılmıştır. Bağımlı değişkenler arasında ne düzeyde ve ne yönde bir ilişki olduğunu belirlemek için "korelasyon analizi" yapılmıştır. Araştırmanın sonuçlarına göre cinsiyet, okul türü, yaş, sınıf, gelir durumu, baba ve anne eğitim durumları öğretmenlik mesleğine yönelik tutum, spor eğitimi aldıkları üniversite değişkenlerine göre istatistiksel olarak anlamlı farklılıklar olduğu görülmüştür. "İşsizlik Kaygısı Ölçeği" ile "Depresyon Ölçeği" arasında pozitif yönde anlamlı ilişkiler gözlenmiştir. "Geleceğe Yönelik Tutum Ölçeği" ile "İşsizlik Kaygısı Ölçeği" ve "Depresyon Ölçeği"nin her biri arasında negatif ve anlamlı ilişkiler belirlenmiştir. Sonuç olarak, üniversitelerde okuyan öğrencilerin mesleklerine tam anlamıyla olumlu bakmamaları beden eğitimi ve spor öğretmenliğinin geleceği açısından endişe verici bir durumdur. Üniversite kurumlarının birlikte çalışması ve istihdamı azaltmak için geleceğe yönelik bir eylem planı hazırlaması faydalı olacaktır.

In this study, the relationship between unemployment anxiety, depression level and attitude toward the future of prospective physical education and sports teachers were investigated. The study was conducted with 610 prospective physical education and sports teachers, who studied at Fırat University, Harran University, Adiyaman University, Agri Ibrahim Cecen University and Bayburt University. To determine the perspective of the study group, the "Unemployment Anxiety Scale", "Depression Scale" and the "Attitude Toward Future Scale" were used. The analyses of the data collected from the scale forms were conducted by using SPSS 24.0 package software. To reveal the distribution of the study group in terms of the demographical variables, frequency, and percentage calculations were conducted. To determine whether the data obtained from the scale and its subscales provided a normality distribution, a normality test was conducted. As a result of the normality test, it was decided to conduct parametric tests. To evaluate the level of differentiation in terms of the independent variables, parametric tests, which included "Independent samples t-test" and "One-way Variance Analysis (ANOVA)", were conducted. Additionally, "Correlation Analysis" was conducted to reveal the level and significance of the relationship between dependent variables. 2 According to the results of the research, it was seen that there were statistically significant differences according to the variables of gender, school type, age, class, income status, father and mother education status, attitude towards the teaching profession, and the university where they received sports education. A positive and significant relationship was observed between the "Unemployment Anxiety Scale" and the "Depression Scale". Negative and significant relationships were determined between each of the "Attitudes towards the Future Scale" and the "Unemployment Anxiety Scale" and "Depression Scale". As a result, it is a worrying situation for the future of physical education and sports teaching that students studying at universities do not have a positive attitude towards their profession. It would be beneficial for university institutions to work together and prepare an action plan for the future to reduce employment. Key Words: Physical Education and Sports, Prospective Teachers, Unemployment, Depression, Future Expectation
Beden eğitimi ve spor öğretmeni adaylarının işsizlik kaygıları, depresyon düzeyleri ve geleceğe yönelik tutumları arasındaki ilişki
Keywords: Spor